2015
DOI: 10.1016/j.newast.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength modelling the SED of supersoft X-ray sources I. The method and examples

Abstract: -New method of modelling the spectra of supersoft X-ray sources is introduced. -The method analyses the X-ray/near-IR spectral energy distribution. -The multiwavelength approach overcomes problems of modelling only the X-ray data. -More trustworthy fundamental parameters are derived. AbstractRadiation of supersoft X-ray sources (SSS) dominates both the supersof X-ray and the far-UV domain. A fraction of their radiation can be reprocessed into the thermal nebular emission, seen in the spectrum from the near-UV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…where the error correspond to the statistical error of the [Fe ] 6374 Å line luminosity. The so obtained value of the WD colour temperature is close to the temperatures ℎ = (2.275 ± 0.3) × 10 5 K and ℎ = (2.50 ± 0.1) × 10 5 K derived previously by Kahabka & Haberl (2006) and Skopal (2015), respectively. In addition, this temperature is in agreement with the simple formula of Iijima (1981) used to estimate the effective temperature of a central source from the nebular emission line fluxes:…”
Section: Colour Temperature Of the White Dwarfsupporting
confidence: 89%
See 1 more Smart Citation
“…where the error correspond to the statistical error of the [Fe ] 6374 Å line luminosity. The so obtained value of the WD colour temperature is close to the temperatures ℎ = (2.275 ± 0.3) × 10 5 K and ℎ = (2.50 ± 0.1) × 10 5 K derived previously by Kahabka & Haberl (2006) and Skopal (2015), respectively. In addition, this temperature is in agreement with the simple formula of Iijima (1981) used to estimate the effective temperature of a central source from the nebular emission line fluxes:…”
Section: Colour Temperature Of the White Dwarfsupporting
confidence: 89%
“…This is possible due to the fact that in the near-IR the emission from the AGB star dominates over the emission from both the WD, which peaks in the UV, and the ionized nebula, which is most prominent in the optical lines (Skopal 2005). Using these parameters Skopal (2015) classified the giant star in LIN 358 to be a type K5 Ib supergiant.…”
Section: Introductionmentioning
confidence: 99%
“…The main simplification of the calculations presented in this paper is the assumption of blackbody spectrum for the post-nova SSSs. This assumption is commonly made in SSS studies; it is motivated, at least partly, by the fact that the observed spectral energy distribution (SED) of the continuum emission in SSSs can be often represented by the simple blackbody spectrum (e.g, Skopal 2015). However, it is obvious that spectral formation in SSSs is much more complex.…”
Section: Discussionmentioning
confidence: 99%
“…(9) of Skopal 2015). Angular radius of the giant, θ g , can be obtained from its observed bolometric flux,…”
Section: Modelling the Sedmentioning
confidence: 99%